2017
DOI: 10.1128/mcb.00561-16
|View full text |Cite
|
Sign up to set email alerts
|

Interchangeable Roles for E2F Transcriptional Repression by the Retinoblastoma Protein and p27KIP1–Cyclin-Dependent Kinase Regulation in Cell Cycle Control and Tumor Suppression

Abstract: The mammalian G 1 -S phase transition is controlled by the opposing forces of cyclin-dependent kinases (CDK) and the retinoblastoma protein (pRB). Here, we present evidence for systems-level control of cell cycle arrest by pRB-E2F and p27-CDK regulation. By introducing a point mutant allele of pRB that is defective for E2F repression (Rb1 G ) into a p27 KIP1 null background (Cdkn1b Ϫ/Ϫ ), both E2F transcriptional repression and CDK regulation are compromised. These double-mutant Rb1 G/G ; Cdkn1b Ϫ/Ϫ mice are v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 45 publications
(68 reference statements)
2
19
0
Order By: Relevance
“…This experiment suggests that pRB is unable to engage E2F3 and CDH1 dependent functions simultaneously, suggesting that these functions are interchangeable. This mirrors findings from recent in vivo approaches to pRB dependent cell cycle control [30], and this will be explored further in the discussion.
Fig. 3Competition between E2Fs and CDH1 for pRB binding.
…”
Section: Resultssupporting
confidence: 72%
“…This experiment suggests that pRB is unable to engage E2F3 and CDH1 dependent functions simultaneously, suggesting that these functions are interchangeable. This mirrors findings from recent in vivo approaches to pRB dependent cell cycle control [30], and this will be explored further in the discussion.
Fig. 3Competition between E2Fs and CDH1 for pRB binding.
…”
Section: Resultssupporting
confidence: 72%
“…We have shown that the Rb1 G mutation exacerbates cancer development in Trp53 −/− mice, but has essentially no effect on tumor-free survival in the presence of oncogenic Kras G12D , or from loss of p21 ( Cdkn1a −/− ). In conjunction with prior results that Rb1 G/G ; Cdkn1b −/− animals succumb to pituitary tumors (18), and that Rb1 +/− ; Cdkn1a −/− mice have accelerated pituitary tumorigenesis (29), these genetic crosses provide two simple conclusions relating to RB function in cell cycle and cancer susceptibility. The first is that compromised RB-E2F transcriptional regulation is not uniformly cancer promoting, even though it potently contributes in some crosses.…”
Section: Discussionsupporting
confidence: 53%
“…3D). This is an important observation as Rb1 +/− ; Cdkn1a −/− mice are susceptible to pituitary tumors and have similar survival as for Rb1 G/+ ; Cdkn1b −/− animals (18, 29), this indicates that the Rb1 G mutation cooperates preferentially with p27 loss.…”
Section: Resultsmentioning
confidence: 71%
“…The exact roles of the individual E2F homologues in cancer progression are not fully understood. E2F1-E2F3 are the central regulators of cell cycle [56]. The activities are negatively regulated via binding with retinoblastoma-like 1 protein (RB; encoded by RBL1).…”
Section: Discussionmentioning
confidence: 99%